Physic Simulation Experiments using Augmented Reality - Surya Sumpeno; Christyowidiasmoro Christyowidiasmoro (Institut Teknologi Sepuluh Nopember, 2014)
Augmented Reality (AR) is a technology which render visual information such as three-dimensional (3-D) virtual objects and allow users to interact with virtual and real object at the same time. This technology can help student to learn intuitively and interactively through simulation which is equipped with AR. This paper discusses the physic simulation such as force, gravity, friction, spring, gears and chain through AR. The system that we built is deployed on mobile platform specifically Android based devices and based on marker-less AR. Instead of a black-and-white square marker, we use image corresponding the context to trigger and visualize the simulation. By simply touch the correspondent image, student can interact and alter the course of the physic simulation.